Prinsip-Prinsip Good Governance dalam Pengelolaan Dana Desa di Desa Tambaksari Kidul, Kecamatan Kembaran, Kabupaten Banyumas - Khofifah Nurul Hidayah; Chamid Sutikno; Indah Ayu Permana Pribadi; Ariesta Amanda; Zaula Rizqi Atika (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to analyze the implementation of Good Governance principles, including accountability, transparency, and participation in the management of Village Funds in Tambaksari Kidul Village, Kembaran Subdistrict, Banyumas Regency. The research method uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that accountability in village financial reporting has been carried out in accordance with regulations, although there are still delays in reporting. Transparency in budgeting and the implementation of village funds has been conducted through village meetings and village information media, but has not yet reached the stage of impact evaluation. Community participation is quite active in planning and implementation, but minimal in the evaluation stage. Challenges faced include limited human resources, infrastructure, and low community participation. Strengthening human resource capacity, improving information transparency, and optimizing inclusive village meetings are needed to support better village fund management.